2020
DOI: 10.1155/2020/2504674
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Acupuncture Treatment on Chemotherapy-Induced Peripheral Neuropathy: A Pilot, Randomized, Assessor-Blinded, Controlled Trial

Abstract: Objective. This pilot study aims to evaluate the effectiveness and safety of acupuncture in the treatment of chemotherapy-induced peripheral neuropathy (CIPN). Methods. This study was a pilot randomized controlled trial, which was conducted with cooperation between Beijing University of Chinese Medicine (BUCM), China, and Tehran University of Medical Science (TUMS), Iran. Forty participants with CIPN were randomly assigned (1 : 1) to receive twelve sessions of acupuncture (20 minutes each session over 4 weeks)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 47 publications
2
52
0
1
Order By: Relevance
“…According to traditional Chinese medicine, acupuncture at ST36 and SP6 have the effect of tonifying blood. Several studies show that stimulation of these two acupoints protects against chemotherapy induced anemia, leukopenia, and other peripheral neuropathies (67)(68)(69)(70)(71). Our results show that EA ST36 and SP6 inhibited the most detrimental effects of cisplatin in normal and cancer mice.…”
Section: Discussionsupporting
confidence: 57%
“…According to traditional Chinese medicine, acupuncture at ST36 and SP6 have the effect of tonifying blood. Several studies show that stimulation of these two acupoints protects against chemotherapy induced anemia, leukopenia, and other peripheral neuropathies (67)(68)(69)(70)(71). Our results show that EA ST36 and SP6 inhibited the most detrimental effects of cisplatin in normal and cancer mice.…”
Section: Discussionsupporting
confidence: 57%
“…The research to date on the effectiveness of CIM for CIPN‐related symptoms has been focused primarily on postchemotherapy acupuncture as a single modality, assessing only subjective outcome measures. The evidence supporting the effectiveness of acupuncture for this indication is compelling 12–14 . Acupuncture activates A‐β, A‐δ, and C afferent fibers, with signals ascending through the spinal ventrolateral column to the sensory‐motor cortex of the brain 15 .…”
Section: Introductionmentioning
confidence: 99%
“…We believe that acupuncture at these acupoints may regulate the gut–brain axis by stimulating the conception vessel to achieve immune regulation and neuroprotection effects. In addition, previous studies have shown that acupuncture at Quchi (LI11), Hegu (LI4), Zusanli (ST36), and Sanyinjiao (SP6) can alleviate the symptoms of limb numbness effectively ( 44 ). However, the specific mechanism is not precise.…”
Section: Discussionmentioning
confidence: 99%